The optimization mechanism for gas hydrate dissociation by depressurization in the sediment with different water saturations and different particle sizes - Li, Xiao-Yan; Li, Xiao-Sen; Wang, Yi; Liu, Jian-Wu; Hu, Heng-Qi (Energy, 2021)
Gas hydrate is considered as a new promising energy resource, and it is extensively distributed in offshore sediments and permafrost region. Two important factors affecting the gas hydrate dissociation are the water saturation in the sediments and the particle size of the sediments. In this study, the influences of the water saturation on the hydrate dissociation by depressurization in the sediments with different particle sizes were analyzed. It was found that there could be an optimum water saturation (Sw,op), at which the hydrate dissociation rate reached to the maximum value. When the water saturation (Sw) was smaller than Sw,op, the hydrate dissociation was mainly limited by the heat transfer rate of the sediments, and the hydrate dissociation rate increased with the increase of the water saturation. When the water saturation (Sw) was larger than Sw,op, the hydrate dissociation rate was limited by the mass transport rate of the gas released from the hydrate dissociation, and the hydrate dissociation rate decreased with the increase of the water saturation. The experimental results showed that for the sediments with the particle size of 40-60 mesh, the optimum water saturation is smaller than 0.042. For the sediments with the particle size of 325-400 mesh, the optimum water saturation is larger than 0.415. For the sediments with the particle size of 105-125 mesh, the optimum water saturation is closed to 0.413. Therefore, the optimum water saturation for hydrate dissociation increased with the decrease of the particle size of the sediments, and it was inferred that the optimum water saturation was related to the irreducible water saturation of the sediments. It was a new knowledge about the influence of the water saturation on the hydrate dissociation in the sediments with different particle sizes, and it could provide some guidance for the production method of gas hydrate in different types of hydrate reservoirs. (c) 2020 Elsevier Ltd. All rights reserved.